Implementation of Wordwall-Based Media as An Effort to Improve the Quality of Mathematics Learning in Elementary Schools - Chairunnisa, Amarylis; Usodo, Budi; Yamtinah, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
According to a survey conducted by the International Student Assessment Program (PISA), it is clear that Indonesia still ranks low compared to other countries. The survey, conducted in 2022, placed Indonesia in 74th place out of 79 countries. This study aims to determine: 1) the application of technology in mathematics learning in elementary schools. 2) teachers' ability to utilize technology in mathematics learning. 3) the quality of wordwall-based learning in mathematics subjects in elementary schools. This type of research is a qualitative case study with data collection techniques including interviews, observations, and questionnaires. The subjects of this study were fourth-grade students, homeroom teachers, and the principal's staff. Data analysis used inductive techniques, including data collection, data reduction, and writing conclusions. Data validity was tested using triangulation of techniques, sources, and time. The results obtained from this study are: 1) the application of technology-based mathematics learning in elementary schools. 2) Almost all teachers are able to utilize technology well. Some teachers have also implemented technology in the teaching and learning process, such as the use of animated videos and illustrated PowerPoints. 3) Wordwall-based learning has been proven to generate renewed enthusiasm for all students, as the quizzes presented are highly engaging and animated. If implemented routinely, wordwall-based learning will improve the quality of learning, particularly in mathematics. With the introduction of technology-based learning in elementary schools, it is hoped that the quality of learning will improve even further.